2016
DOI: 10.1002/polb.23988
|View full text |Cite
|
Sign up to set email alerts
|

Design of bicontinuous donor/acceptor morphologies for use as organic solar cell active layers

Abstract: In recent works, we demonstrated the achievement of bicontinuous donor/acceptor morphologies by the addition of conjugated block copolymers to a blend of conjugated homopolymer donors and fullerene acceptors. However, the domain sizes resulting in experiments were much larger than those of interest for high‐performance organic solar cells. Moreover, a significant concentration of fullerene acceptors was present in the donor domains. Here, we utilize simulations to study the bicontinuous donor/acceptor morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…A strategy to control the nanostructure and improve the stability of OPVs is to design conjugated block copolymers (CBCPs) where one block is an electron-donating polymer and the other block is an electron-accepting polymer. Because of the potential for controlled assembly driven by thermodynamics dictated by the molecular characteristics of the blocks, CBCPs could lead to morphologically stable BHJs. , For instance, in-plane lamellar order of donor and acceptor domains could provide the interfacial area necessary for charge generation and, at the same time, the p- and n-type transport channels required for efficient collection of photogenerated charge carriers. BCPs can also be used as additives and interfacial stabilizing agents in ternary blend cells. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A strategy to control the nanostructure and improve the stability of OPVs is to design conjugated block copolymers (CBCPs) where one block is an electron-donating polymer and the other block is an electron-accepting polymer. Because of the potential for controlled assembly driven by thermodynamics dictated by the molecular characteristics of the blocks, CBCPs could lead to morphologically stable BHJs. , For instance, in-plane lamellar order of donor and acceptor domains could provide the interfacial area necessary for charge generation and, at the same time, the p- and n-type transport channels required for efficient collection of photogenerated charge carriers. BCPs can also be used as additives and interfacial stabilizing agents in ternary blend cells. , …”
Section: Introductionmentioning
confidence: 99%
“…Many BCPs have a donor block based on poly­(3-hexyl­thiophene) because of its ease of synthesis and known performance in OPVs. ,,,,, P3HT is a semicrystalline polymer with a relatively high melting point (>200 °C), and in many cases, the phase separation observed in its BCPs with amorphous coil blocks is driven by its crystallization, limiting the ability to control structure by thermal processing . In CBCPs both blocks may be semicrystalline with high melting points, leading to more complex phase behavior. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this approach, a connection between local and global morphology can be made precisely because well-defined mapping definitions allow a direct conversion between the atomistic and CG models. Other methods (e.g., lattice-based approaches) have also been used in the modeling of the global morphology of OSCs [50][51][52][53][54][55][56], but the conversion of the global morphology into an atomistic representation is not straightforward with these techniques.…”
Section: From Local To Global Morphologymentioning
confidence: 99%
“…6 Finally, in a more recent study, we identified a large collection of blend formulations that should give rise to such bicontinuous phases and identified which of these select blend formulations result from comparable volume mixtures of donors and acceptors that simultaneously yield the smallest and most compositionally pure donor and acceptor domains. 7 While our previous studies demonstrated that BCP additives can be utilized to target equilibrium bicontinuous morphologies with the characteristics desired for organic photovoltaic applications, it is yet unclear whether such structures yield improved device performance when compared to other idealized morphologies with the features believed to be optimal for device performance. For instance, theoretical studies have suggested that columnar morphologies with domains oriented perpendicular to the electrode outperform bicontinuous gyroid morphologies due to smaller geminate charge recombination in the former case.…”
Section: Introductionmentioning
confidence: 99%